Thermodynamic properties of liquid mixtures. III. Acetone-water - Benedetti, Assis Vicente [UNESP]; Cilense, M. [UNESP]; Vollet, D. R. [UNESP]; Montone, R. C. [UNESP] (Elsevier, 1993)
The excess enthalpy of mixing of acetone-water was measured at 25°C in the 0-1 molar fraction range. The minimum and the maximum in the H E (X 2) curve occurred at X 2 = 0.18 and X 2 = 0.85, respectively. The excess partial molar and other excess quantities were also calculated for the acetone-water system at 25°C. The results are interpreted in view of the influence of acetone on the structure of water. © 1983.